2019
DOI: 10.3747/co.26.5085
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Canadian Patients and Physicians for Adjuvant Treatments for Melanoma

Abstract: Background Past research suggests that patients with early- and late-stage melanoma will endure adverse events and inconvenient treatment regimens for improved survival. Evidence about the preferences of Canadian patients and physicians for novel adjuvant treatments for melanoma is unavailable.Methods Patient and physician preferences for adjuvant treatments for melanoma were assessed in an online discrete choice experiment (dce). Treatment alternatives were characterized by 8 attributes with respect to dosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Most studies (n = 70, 89%; e.g. [36,43,51,64,95]) were conducted in one country, with three studies (4% [50,84,97]) conducted in two countries and six (8% [39,41,58,75,110,111]) conducted in three countries. No study included more than three countries.…”
Section: Search Resultsmentioning
confidence: 99%
“…Most studies (n = 70, 89%; e.g. [36,43,51,64,95]) were conducted in one country, with three studies (4% [50,84,97]) conducted in two countries and six (8% [39,41,58,75,110,111]) conducted in three countries. No study included more than three countries.…”
Section: Search Resultsmentioning
confidence: 99%
“…The improved RFS [ 9 , 10 , 18 ], as well as the experience in adverse-event management already gained in the advanced metastatic setting, might have been reasons for the rapid and high acceptance of adjuvant ICI and TT by physicians. A recent Canadian cross-sectional survey confirmed that patients considered RFS the most important and OS the second most important attribute of adjuvant treatment, and preferred active treatment to follow-up alone [ 25 ]. In our cohort, the tumor board decided against adjuvant treatment only in very few cases due to patients´ comorbidities or low sentinel tumor burden, reflecting physicians’ attitudes toward the safety and efficacy of current adjuvant therapy options.…”
Section: Discussionmentioning
confidence: 99%
“…When the total choice sets were beyond the cognitive capability of respondents, the blocking technique was used to reduce the number of choice tasks in one questionnaire [13]. Seven studies (21%) included opt-out or status quo options [43,44,53,[56][57][58][59].…”
Section: Methodsmentioning
confidence: 99%